Pharmacogenetics of Antidepressants - Crisafulli, Concetta; Fabbri, Chiara; Porcelli, Stefano; Drago, Antonio; Spina, Edoardo; De Ronchi, Diana; Serretti, Alessandro (Frontiers in Pharmacology, 2011)
Up to 60% of depressed patients do not respond completely to antidepressants (AD) and up to 30% do not respond at all. Genetic factors contribute for about 50% of the AD response. During the recent years the possible influence of a set of candidate genes as genetic predictors of AD response efficacy was investigated by us and others. They include the cytochrome P450 (CYP) superfamily, the P-glycoprotein (ABCB1), the tryptophan hydroxylase (TPH), the catechol-O-methyltransferase (COMT), the monoamine oxidase A (MAOA), the serotonin transporter (5-HTTLPR), the norepinephrine transporter (NET), the dopamine transporter (DAT), variants in the 5HT1A, 2A , 3A, 3B and 6 receptors, adrenoreceptor beta-1 (ADRB1) and alpha-2 (ADRA2A), the dopamine receptors (D2), the G-protein beta3-subunit (GNB3), the corticotropin releasing hormone (CRH) receptors (CRHR1 and CRHR2), the glucocorticoid receptors (GR), the c-AMP response-element binding (CREB) and the brain-derived neurotrophic factor (BDNF). Marginal associations were reported for angiotensin I converting enzyme (ACE), circadian locomoter output cycles kaput protein (CLOCK), glutamatergic system, nitric oxide synthase (NOS) and interleukin 1-beta (IL-1beta) gene. In conclusion, gene variants seem to influence human behavior, liability to disorders and treatment response. Nonetheless, gene x enviroment interactions have been hypothesized to modulate several of these effects.